From Causal Mechanisms to Policy Mechanisms: Why Did Crime Decline and What Lessons Can Be Learned from It? - Roman, John K. (American journal of criminal justice, 2022)
Criminology has not systematically identified the cause or causes of perhaps the most seminal event in crime and justice of the last half century: the crime decline of the 1990s. This paper uses a causes-of-effects analysis to infer the mechanisms of the crime decline. This is not a purely academic exercise—there has been a large increase in violence, particularly gun violence at the beginning of the 2020s. Identifying the mechanisms of the last crime decline can inform the development of contemporary strategies. Here, two classes of crime decline causes are proposed: mechanisms that are endogenous to the criminal law system and mechanisms that are exogenous to it. The latter class includes impacts of changes in macroeconomics, consumer behavior, and public interest policy where positive externalities that arose from those factors contributed to the crime decline. A descriptive effect of causes analysis suggests that these exogenous mechanisms contributed disproportionately to the crime decline as compared to endogenous mechanisms. Further, consumer behavior and public interest externalities are well aligned with potential policy levers and particularly salient to current and future efforts to reduce crime and violence prospectively. The analysis suggests that efforts to improve public safety require policies that fall outside of traditional criminal justice approaches.